Research Progress and Future Prospects of Three Oncolytic Viruses in the Treatment of Melanoma - Fang, Lizhou (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Melanoma is one of the more common tumors among young people, and the number of deaths caused by melanoma is increasing year by year. How to find efficient and safe treatment methods is currently a problem that needs to be solved. At present, most melanoma patients are treated through surgical resection, but the recurrence rate is higher and the effect is poor. Research has found that oncolytic virus therapy alone or in combination with other methods (radiotherapy, cell therapy, immunotherapy) not only has a high acceptance rate for patients, but also has a lower recurrence rate due to better healing. The three viruses that are currently being studied extensively are herpes simplex virus, Coxsackie virus, and vesicular stomatitis virus. In the future, it may become a first-line treatment method. This article mainly discusses the current research progress and therapeutic effects of three viruses, as well as the research on their corresponding variants. Provide corresponding suggestions for future development direction.